Dry matter intake, performance, carcass traits and expression of genes of muscle protein metabolism in cattle fed increasing levels of de-oiled wet distillers grains - Ferreira, Mateus [UNESP]; Niehues, Maria Betania [UNESP]; Tomaz, Lais Aquino [UNESP]; Baldassini, Welder [UNESP]; Ladeira, Marcio; Arrigoni, Mario [UNESP]; Martins, Cyntia Ludovico [UNESP]; Gionbelli, Tathyane; Paulino, Pedro; Machado Neto, Otavio R. [UNESP] (Elsevier B.V., 2020)
The supply of we distillers grains (WDG) has been growing in Brazil, with the increase in corn ethanol production. Thus, the aim of this study was to evaluate the effect of de-oiled corn WDG in the diet of feedlot cattle on DMI, performance, carcass traits, meat quality and expression of genes involved in the muscle protein metabolism. One hundred non-castrated F1 Angus-Nellore bulls, aged 20-24 months, with average IBW of 369.58 +/- 49.17 kg, were used in a randomized complete block design. The animals were fed diets containing 0, 150, 300 and 450 g/kg de-oiled WDG (40 g/kg ofEE) replacing corn and soybean meal. After 129 days on feed, the animals were slaughtered and LT muscle samples were collected for molecular biology assays. Muscle protein metabolism genes such as eIF4, IGFR1, mTOR, GSK3f3 and P70S6K were investigated by RTqPCR. Data were analyzed using polynomial contrasts (linear, quadratic and control versus WDG). The inclusion of by-product improved DMI and FBW (P < 0.05). A tendency (P < 0.10) to a quadratic effect was observed on DMI and FBW, with greater values for animals fed diet with 150 and 300 g/kg of WDG. The animals fed WDG presented greater HCW and CCW (P < 0.05), and there was a quadratic effect (P < 0.05) for the REA, with greater values for the animals fed diet with 300 g/kg of WDG. Moreover, no differences were observed in BFT and carcass pH, and the meat quality traits were similar (P > 0.05) among treatments (SF, CL, ILC, MFI, and WHC). However, the inclusion of WDG led to a reduction in the expression of eIF4, mTOR and IGFR1 genes (P < 0.05). Overall, meat quality traits were not affected by nutritional treatments. Although increased levels of de-oiled WDG influenced DMI, FBW, carcass weights and REA (an indicator of muscle deposition) in response to feeding, it did not produce concerted changes in genes of LT related to muscle protein metabolism.
Keywords: Animal nutrition; beef cattle; feedlot; meat quality; molecular biology